IDENTIFIKASI POTENSI WILAYAH UNTUK PENGEMBANGAN EKONOMI MASYARAKAT SEKITAR KAWASAN TAMAN NASIONAL KERINCI SEBLAT (TNKS): STUDI KASUS KECAMATAN RIMBO PENGADANG KABUPATEN LEBONG PROVINSI BENGKULU - Windirah, Nola; Arianti, Nyayu Neti (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2013)
This research aimed to analyze 1) the potential area in Rimbo Pengadang Subdistrict Lebong District and 2) which potential area can be developed become the alternatives of economic activities to the sub-district communities. The benefit expected was the community of Rimbo Pengadang Sub-district may do economic activities on those potential areas and the infringement of The Kerinci Seblat National Park may be decreased. The secondary data were used and analiyzed by Flow Model qualitative method. There were four steps in Flow Model such as Data Collection, Data Reduction, Data Display and Conclusion. The research gave these results 1) the potential areas in Rimbo Pengadang Sub-district Lebong District were Community Forest and Natural Pasture, and 2) those potential areas could be developed become the business activities for the communities because of the supporting factors more than the inhibiting factors.